AN L-GLUTAMINE REQUIREMENT FOR INTERCELLULAR ADHESION - Oppenheimer, Steven B. (1969)
Intercellular adhesion presumably involves components of the cell surface, but the chemical nature of these substances is not known. The present studies suggest that complex carbohydrates are required for the adhesion of at least one type of animal cell. Single cells obtained from “embryoid bodies,” the ascites-grown form of a mouse teratoma, aggregated in a complex tissue culture medium, but not in a glucose balanced salts solution. The active component of the tissue culture medium was identified as L-glutamine, and the only compounds found to replace it were the hexosamines D-glucosamine and D-mannosamine. A variety of studies indicated that the three compounds were active as a consequence of metabolic reactions. These results are consistent with known metabolic pathways and indicate that the conversion of nonadhesive to adhesive teratoma cells requires the synthesis of glycoproteins, glycolipids, and/or polysaccharides.